Arrhenian growth thermodynamics in a marine-derived tropical Fusarium equiseti and polar Pseudogymnoascus spp. in a liquid culture system - Tajuddin, Natasha; Rizman-Idid, Mohammed; Convey, Peter; Alias, Siti Aisah (Elsevier, 2019)
We hypothesised that the activation energy (Ea) of growth in a marine-derived tropical strain of Fusarium equiseti and polar strains of Pseudogymnoascus spp. grown for 10 days in a liquid culture system comprised of seawater Mueller-Hinton Broth would differ across the same experimental culture temperature range. The specific growth rates (SGRs) obtained from these experiments were fitted into third-degree polynomial and Brière-2 temperature-dependent models to estimate optimum temperatures for growth (Topt) and maximum SGR (SGRmax) of the selected strains. Estimates of SGR values from the Brière-2 model were used to calculate the temperature coefficient (Q10) and Ea for growth in all three fungal strains across the experimental culture temperature range. Our findings indicated that F. equiseti is better adapted to utilising higher levels of thermal energy for growth than either Pseudogymnoascus strain, consistent with general definitions that classify the former as a mesophile and the latter as psychrophiles. A progressive increase in pH was recorded in the liquid culture system during the growth of F. equiseti and Pseudogymnoascus spp., suggesting that these strains could tolerate more alkaline conditions for growth until nutrient resources were exhausted, as has been noted in some other fungal studies. © 2018 Elsevier B.V. and NIPR